Determining the relationship between e-health literacy and personal health system and patient satisfaction using structural equation model: an example of a training and research hospital - Mehmet Koca; Feyza İnceoğlu; Serdar Deniz (BMC Health Services Research)
Abstract Background In the current technology landscape, several individuals electronically stores their health information. The personal health system offers significant conveniences to users, hence enhancing patient satisfaction. Assessing the impact of e-health literacy, personal health system, and patient happiness on enhancing patient satisfaction an essential outcome of health services is crucial for system improvement and clarity. This study sought to assess the impact of patients’ e-health literacy levels, evaluated at a training and research hospital, on personal health systems and patient satisfaction. Methods The research was carried out in a teaching and research hospital associated with the Ministry of Health in Malatya province from March 15, 2024, until April 25, 2024. The research was executed with data from 275 people. The data collection form consists of 4 sections. Results In the present study, 275 people participated, and 57.8% of them were women. 3.69 were the mean score for the personal health system utilization perception, 92.64 was the mean score for the outpatient satisfaction scale, and 3.63 were the mean score for the e-health literacy scale. E-health literacy explained 2% (R2 = 0.02) of outpatient satisfaction and e-health literacy and outpatient satisfaction explained 30% (R2 = 0.30) of the perception of personal health system use. Conclusion Outpatient satisfaction influences individuals’ perceptions of their health system, e-health literacy affects outpatient satisfaction, and outpatient satisfaction serves as a mediator between e-health literacy and personal health system perspectives.